Smooth Muscle Cell–Specific PKM2 (Pyruvate Kinase Muscle 2) Promotes Smooth Muscle Cell Phenotypic Switching and Neointimal Hyperplasia. Issue 5 (11th March 2021) - Jain, Manish; Dhanesha, Nirav; Doddapattar, Prakash; Nayak, Manasa K.; Guo, Liang; Cornelissen, Anne; Lentz, Steven R.; Finn, Aloke V.; Chauhan, Anil K.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: The role of glycolytic enzyme PKM2 (pyruvate kinase muscle 2) in smooth muscle cell (SMC) phenotype switching and neointimal hyperplasia is poorly understood. We determined the role of PKM2 in SMC phenotype switching and neointimal hyperplasia. Approach and Results: We show that PKM2 is expressed in the SMC-rich neointima of the murine carotid artery and peri-strut areas in bare-metal stented human coronary arteries. PDGF-BB (platelet-derived growth factor-BB) stimulation upregulates the expression of PKM2 in cultured murine and human coronary SMC. To provide conclusive evidence for PKM2 in SMC function, we generated SMC-specific PKM2 −/− mutant strain. We report that PKM2 deletion in SMC reduces injury-induced neointimal hyperplasia by inhibiting SMC proliferation and migration, suppressing synthetic phenotype, and reducing aerobic glycolysis associated with decreased ERK (extracellular signal-regulated kinase), mTOR (mammalian target of rapamycin), and STAT3 (signal transducer and activator of transcription 3) signaling. Furthermore, we show that nuclear PKM2 interacts with STAT3 and β-catenin and regulates transcription of MEK5 (mitogen/extracellular signal-regulated kinase kinase-5), cyclin D1, GLUT1 (glucose transporter 1), and LDHA (lactate dehydrogenase A). Treatment of human coronary SMC with ML265, an activator that induces PKM2 tetramerization and blocks its nuclear translocation, inhibited proliferation, migration, and phenotypic switching. Perivascular application of PKM2 activator reduced neointimal hyperplasia in mice. Conclusions: These findings reveal that PKM2 is a key regulator of SMC function in vascular remodeling and implicates PKM2 as a potential target to reduce neointimal hyperplasia.